Democracy and lifelong learning in Africa - Chimere Okechukwu Iheonu; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
Education has been cited in both theoretical and empirical literature as a key driver of socioeconomic growth. African educational outcomes, however, continue to be subpar at all levels. This study examines the impact of democracy on lifelong learning in 52 African countries from 1990 to 2020, employing Fixed Effects regressions. Six democracy indicators, which include electoral, liberal, participatory, deliberative, egalitarian, and total democracy, derived from the principal component analysis (PCA), are employed in the study. The study also utilizes four education variables to capture lifelong learning in Africa and includes primary, secondary, and tertiary school enrolment, as well as a lifelong learning index derived from the PCA. The findings reveal that improving the quality of democracy in Africa can significantly enhance primary school enrolment. The study also finds that improving electoral, participatory, and egalitarian democracy significantly improves secondary school enrolment in the presence of endogeneity. Additionally, improving egalitarian democracy significantly spurs tertiary education. These findings show the importance of political institutions in enhancing educational attainment and lifelong learning in Africa.
Keywords: 330; Democracy; Lifelong Learning; Africa; Fixed Effects Model; Instrumental Variable